Escherichia coli Dysbiosis Correlates With Gastrointestinal Dysfunction in Children With Cystic Fibrosis. (30th October 2013) - Hoffman, Lucas R.; Pope, Christopher E.; Hayden, Hillary S.; Heltshe, Sonya; Levy, Roie; McNamara, Sharon; Jacobs, Michael A.; Rohmer, Laurence; Radey, Matthew; Ramsey, Bonnie W.; Brittnacher, Mitchell J.; Borenstein, Elhanan; et al.
Abstract: Cystic fibrosis gastrointestinal disease includes nutrient malabsorption and intestinal inflammation. We show that the abundances of Escherichia coli in fecal microbiota were significantly higher in young children with cystic fibrosis than in controls and correlated with fecal measures of nutrient malabsorption and inflammation, suggesting that E. coli could contribute to cystic fibrosis gastrointestinal dysfunction.